Berichtigungsliste der Griechischen Papyrusurkunden Aus Ägypten. - Bakker, Marja J..; Hengstl, Joachim (1943-....).; Hoogendijk, Francisca A. J..; Rupprecht, Hans-Albert.; Worp, Klaas Anthony. (Berichtigungsliste der Griechischen Papyrusurkunden aus Ägypten, 2009)
The Berichtigungsliste der Griechisen Papyruskunden aus Ägypten , compiled under the auspices of the 'Association Internationale de Papyrologues', is an indispensable tool for any editor or user of Greek papyrus documents. Like its predecessors, this twelfth volume lists, in alphabetical order of papyri, the new corrections of readings and datings of published documents, as well as supplementary information, as they have appeared in recent literature. The book is supplied with indexes of new readings and rejected readings of Greek words. The value of the book lies in providing an overview of the explosive growth of research in Greek papyrology, the fruits of which appear in such an extremely wide spectrum of publications, that it may not completely be known or available to professional papyrologists, let alone to historians and philologists who also make use of papyrological resources. Herausgegeben von H.-A. Rupprecht andamp; K.A. Worp. Zusammengestellt von F.A.J. Hoogendijk. Unter Mitarbeit von M.J. Bakker andamp; J. Hengstl